PATH-39. ASSOCIATIONS OF GENOMIC SUBGROUP WITH RECURRENCE IN LOW-GRADE MENINGIOMAS. (9th November 2020) - Youngblood, Mark; Miyagishima, Danielle; Jin, Lan; Gupte, Trisha; Li, Chang; Duran, Daniel; Montejo, Julio; Zhao, Amy; Sheth, Amar; Tyrtova, Evgeniya; Özduman, Koray; Iacoangeli, Francesco; et al.
Abstract: Up to 80% of meningiomas are classified as clinically low-grade, however, a subset of these 'benign' cases will ultimately recur and require additional treatment. The role of molecular subgroup in meningioma recurrence has not been thoroughly investigated, despite correlations of this variable with other clinical features. Indeed, epigenetic and transcriptional evidence supports involvement of distinct oncogenic processes within each subgroup, and as shown in other brain tumors, this may result in divergent clinical courses. In the present study, we classified 429 meningiomas into six established molecular subgroups based on genomic driver, and investigated associations of each subgroup with tumor recurrence. At two years of follow-up, we observed differences in progression free survival curves among relatively aggressive (NF2-loss, PI3K-activated, Hedgehog-activated) and quiescent (KLF4-mutant, SMARCB1-mutant, POLR2A-mutant) subgroups (log rank p = 4.3 x 10 -2 ), with the former group recurring at a rate 14x higher. We found PI3K-activated meningiomas recurred significantly earlier than other subgroups (average time to recurrence of 19.2 months; p = 2.2 x 10 -2 ), though we observed an intermediate long-term outcome relative to the Hedgehog and NF2 lesions. Overall, Hedgehog tumors recurred significantly more frequently than other low-grade meningiomas (adj. p = 3.1 x 10 -2 ), and this subgroup was found to be an independent predictor of progression free survival using cox proportional hazards modelling (HR = 3.1; p = 2.4 x 10 -2 ). By contrast, the aggressiveness of NF2 meningiomas was found to depend upon gender, WHO grade, and elevated Ki-67 index, and this subgroup was not an independent prognostic predictor. Our results suggest molecular subgroup is predictive of recurrence in low-grade meningiomas, and thus is an important consideration in post-operative management decisions. Routine genotyping to detect Hedgehog and PI3K mutant lesions may identify patients that would benefit from closer follow-up and consideration of adjuvant therapies.